TELAAH FIQH MUAMALAH TERHADAP PRAKTIK PEMBIAYAAN MURABAHAH DI LEMBAGA KEUANGAN SYARIAH - Fauziyah Mulyana Putri; Nadia Saphira; Muhammad Miqdad; Muhammad Jalil (Taksasila Edukasi Insani, 2025)
This study aims to analyze the implementation of the murabahah contract in Islamic economics from the perspective of the Qur’an and Hadith. Murabahah is one of the most commonly used sale and purchase contracts in Islamic financial institutions. However, in practice, various deviations are often found, making murabahah resemble interest-based systems used in conventional banking. This research employs a qualitative method using a literature study approach by examining relevant Qur’anic verses, Prophetic traditions (hadith), scholarly opinions, and literature on fiqh al-mu'amalat. The findings indicate that murabahah is permissible in Islam as long as it adheres to the principles of honesty, price transparency, and mutual agreement between both parties. A properly applied murabahah contract reflects justice in economic transactions and upholds Islamic ethical values. Therefore, it is essential for Islamic financial institutions to fully implement Sharia principles in every murabahah contract.Keywords : Islamic economics, Hadith, Murabahah, Qur’an, Sharia contract